Literature as Periscope: Using Narrative Discussion to Cultivate Empathy and Moral Reasoning in Students - Ismail Ismail; Fatmawati Fatmawati (Universitas Muhammadiyah Enrekang, 2025)
In an era marked by declining empathy and growing social polarization, education faces an urgent task to nurture moral sensitivity and intercultural understanding. This study explores how narrative discussion of literature can foster empathy and moral reasoning among pre-service English teachers in a rural Indonesian university. Adopting a mixed-methods design, the research involved 20 undergraduate students who participated in a six-week intervention integrating literary reading, guided group dialogue, and reflective writing. Quantitative data from the Interpersonal Reactivity Index (IRI) and Defining Issues Test-2 (DIT-2) were analyzed using paired-sample t-tests, while qualitative data from reflective journals and classroom observations underwent thematic analysis. Results revealed significant improvements in empathy (t(19) = 8.26, p < .001, d = 1.85) and moral reasoning (t(19) = 7.48, p < .001, d = 1.67). Thematic findings highlighted emotional resonance, perspective transformation, and ethical sensitivity as key processes underlying moral growth. The study introduces the Narrative-Driven Empathy Formation Model (NDEFM), explaining how narrative engagement, dialogic reflection, and ethical internalization interact to cultivate moral awareness. Situated within a Southeast Asian, collectivist context, this research extends global theories of moral education by demonstrating that literature-based pedagogy can serve as a culturally responsive approach to developing empathy and ethical reasoning. The findings underscore the potential of literature as both a pedagogical and moral periscope—enabling students to explore, reflect, and act upon the moral complexities of human experience.